Epithelial stem cell exhaustion in the pathogenesis of idiopathic pulmonary fibrosis - Chilosi, M.; Doglioni, C.; Murer, et al., B. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
New paradigms have been recently proposed in the pathogenesis of idiopathic pulmonary fibrosis (IPF), evidencing that in IPF the cumulative action of an accelerated parenchymal senescence determined by either telomere dysfunction or genetic defects, together with the concurrent noxious activity of tobacco smoking, are able to severely compromise the regenerative potential of parenchymal epithelial stem cells, triggering a cascade of molecular signals and events (scarring, bronchiolar proliferation, abnormal remodelling) eventually leading to severe and irreversible functional impairment.New pathogenic schemes focus on the complex molecular mechanisms driving in a vicious circle the different signalling pathways (e.g.Wnt/ -catenin, TGF-beta, caveolin-1, etc.) potentially involved in epithelial-mesenchymal transition and irreversible lung remodelling.